PENENTUAN DAERAH PENANGKAPAN IKAN TONGKOL (Euthynnus affinis) BERDASARKAN SEBARAN SUHU PERMUKAAN LAUT DI PERAIRAN IDI RAYEUK KABUPATEN ACEH TIMUR - Syamsunnisak Syamsunnisak; Alvi Rahmah; Musri Musman (Universitas Syiah Kuala, 2016)
This study aimed to determine the potential fishing ground for tuna by remote sensing based on sea surface temperature in the waters of Idi Rayeuk, East Aceh regency. The Collection of field data in such as the number of catches and the coordinates of the fishing conducted from March to April 2016. Sea surface temperature downloadable on the site http://oceancolorgsfc.nasa.gov. Then processed using the device Seadas 7.3. The result showed that the distribution of sea surface temperatures in the waters of Idi Rayeuk from March to April 2016 ranges from 28°C to 30°C with the average of sea surface temperature was 29°C. There were two potential fishing ground identified during the study in East Aceh regency District of Idi Rayeuk, e.i 1) at the coordinates 5°04'88